Agriculture in the Western Balkan countries - Tina Volk (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2010)
The current publication covers Albania, Bosnia-Herzegovina, Croatia, Kosovo under UNSCR 1244/99, the FYR Macedonia, Montenegro and Serbia, and provides an overview of the agricultural situation in the European Union (EU) candidate and potential candidate countries of the Western Balkans (WBs). The objective was to provide an analysis of the development and current situation in agriculture and agricultural policy in these countries as relates to the EU accession process. The individual country reports, as well as a cross-country overview and comparison, have been prepared as a part of 'AgriPolicy' project, which was financially supported by the European Commission under the 7th framework program. CONTENTS: PREFACE ... I; EXECUTIVE SUMMARY... 1, Tina Volk, Miroslav Rednak, Emil Erjavec; CHAPTER 1: Western Balkan agriculture and agricultural policy - Cross-country overview and comparison... 7, Tina Volk, Miroslav Rednak, Emil Erjavec; CHAPTER 2: Review of agriculture and agricultural policy in Albania... 37, Roland Cela, Shkelzen Marku, Drini Imami; CHAPTER 3: Review of agriculture and agricultural policy in Bosnia and Herzegovina ... 63, Sabahudin Bajramović, Dragana Ognjenović, Aleksandra Nikolić; CHAPTER 4: Review of agriculture and agricultural policy in Croatia ... 93, Ornella Mikuš, Željka Mesic, Marija Cerjak; CHAPTER 5: Review of agriculture and agricultural policy in Kosovo under UNSCR 1244/99... 123, Muhedin Nushi; CHAPTER 6: Review of agriculture and agricultural policy in FYR Macedonia... 145, Dragi Dimitrievski, Nenad Georgiev, Ana Simonovska, Aleksandra Martinovska Stojceska, Ana Kotevska; CHAPTER 7: Review of agriculture and agricultural policy in Montenegro ... 165, Božidarka Marković, Milan Marković; CHAPTER 8: Review of agriculture and agricultural policy in Serbia ... 189, Natalija Bogdanov, Dragica Bozic; CHAPTER 9: Agricultural policy measures template - A tool for classifying and analyzing agricultural policy measures ... 219, Miroslav Rednak, Tina Volk
urn:nbn:de:gbv:3:2-10874
Keywords: 330; Landwirtschaft; Agrarpolitik; EU-Erweiterung; Albanien; Bosnien-Herzegowina; Kroatien; Kosovo; Mazedonien; Montenegro; Serbien; Südosteuropa